Advancement of orthodontic and craniofacial research sites in the last three decades - Gobichettipalayam Jagatheeswaran Anbuselvan; Muthukumar Karthi; Subramani Raja; Krishnan Prabhakar; Mehaboob Basha Nazaragi Mahabob (Wolters Kluwer Medknow Publications, 2012)
Background: Scientific literature has grown tremendously in past five decades in volume as well as content. This communication enlightens young dentist and scientist about availability of scientific literature in digital format and on the web since it has become impossible to maintain literature in printed format due to sheer volume and content. Materials and Methods: The key words were searched in www.google.com. Result: Out of 3500 results relevant web pages was selected by the authors unanimously. Conclusion: This article was primarily written to create awareness among young dentists and orthodontists the availability of varied orthodontic literature and contributors and journals in disseminating knowledge and opportunities.